Visibilidades e visualidades da velhice na fotografia contemporânea - Santos Junior, João Batista Lemos dos (2016)
The objective of this research is to discuss the visibilities and visualities of old age, focusing on contemporary artistic production and its consequences in photographic production, specifically in the work Cette femme là (1984-1987) of the British photographer John Coplans and A Self-Portrait (1983-1987) of the French Yves Trémorin. In understanding the concept of visibility and visuality we can take into consideration that in a world increasingly filled with images, they are not free or random, which provides a constant mediation between the viewer and reality. This mediation with the symbolic domain leads to an instance in which the visual exceeds a restricted barrier to physical / physiological domain of perception, building along with the cognitive process a complex network in which the see and be seen are closely linked in different instances the social context.